Features of The Disease Management in the Appendical Infiltrate - Ismailov F.M.; Dolim K.S; Askarov T.A (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Acute appendicitis represents the most prevalent acute abdominal pathology requiring surgical intervention. Specific Background: Appendicular infiltrate, occurring in 1-10% of acute appendicitis cases, poses diagnostic challenges that frequently result in inappropriate treatment selection and unjustified surgical procedures. Knowledge Gap: Despite its clinical significance, standardized diagnostic criteria and management protocols for appendicular infiltrate remain inadequately defined, particularly regarding intraoperative recognition and intervention decisions. Aims: This study analyzed diagnostic approaches and treatment outcomes in patients presenting with appendicular infiltrate to establish evidence-based management protocols. Results: Among 3,567 patients treated for acute appendicitis between 2020-2024, appendicular infiltrate was identified in 38 cases (1.1%). Delayed presentation constituted the primary etiological factor (75%), while atypical appendiceal positioning complicated diagnosis in 7.9% of cases. Conservative management achieved successful resolution in 78.9% of patients, whereas 21.1% required surgical intervention due to abscess formation. Intraoperative identification of infiltrate in six patients necessitated procedure termination with drainage placement; one attempted appendectomy resulted in postoperative complications. Novelty: This investigation establishes that immediate cessation of surgery upon intraoperative infiltrate recognition minimizes complications. Implications: These findings emphasize prioritizing conservative management and avoiding appendectomy when infiltrate is encountered operatively.Highlight : Late patient presentation is the primary factor in the development of appendicular infiltrate. Diagnostic difficulties, including atypical appendix location, often lead to tactical errors. Conservative management is effective in most cases, while unjustified appendectomy increases postoperative complications. Keywords : Acute Appendicitis, Appendicular Infiltrate, Delayed Diagnosis, Conservative Treatment, Surgical Tactics